Comparison of Azithromycin versus Erythromycin for Prolongation of Latency in Pregnancies Complicated by Preterm Premature Rupture of Membranes - Finneran, Matthew M.; Appiagyei, Ashley; Templin, Megan; Mertz, Heather (American Journal of Perinatology, 2017)
Objective To assess the impact on the duration of latency to delivery when a single oral dose of azithromycin is substituted for erythromycin in the standard antibiotic regimen used in pregnancies complicated by preterm premature rupture of membranes (PPROM).Study Design A retrospective cohort study of singleton pregnancies complicated by PPROM between 23 and 33 6/7 weeks of gestation from January 2012 to June 2016. Patients prior to June 2014 received a standard antibiotic regimen of 7 days of erythromycin and ampicillin/amoxicillin. After this period, patients received a single oral dose of azithromycin 1 g substituted for erythromycin in this regimen. Primary outcome was latency from PPROM to delivery.Results One hundred sixty-two women met the inclusion criteria, 84 in the erythromycin group and 78 in the azithromycin group. There was no difference in the median latency from PPROM to delivery between the groups (erythromycin: 6.37 days, interquartile range [IQR]: 3.59–10.93 vs. azithromycin: 5.86 days, IQR: 3.12–12.05, p = 0.75). There was a higher rate of cesarean delivery (48.8 vs. 29.5%, p = 0.01) and positive neonatal blood cultures (13.6 vs. 4.1%, p = 0.05) in the erythromycin group.Conclusion There is no difference in latency to delivery when a single oral dose of azithromycin 1 g is substituted for erythromycin in the standard antibiotic regimen used in singleton pregnancies complicated by PPROM.
Keywords: azithromycin; erythromycin; latency; preterm premature rupture of membranes; antibiotics; preterm prelabor rupture of membranes